PMC Turbo image and lidar data taken in July 2018, supplement to Geach et al. (2020) "Gravity Wave and Vortex Ring Formation Observed by PMC Turbo" - Geach, Christopher P (Data Repository for the University of Minnesota (DRUM), 2020)
These datasets are published in accordance with AGU requirements for journal submission.
Data consist of image data ("Geach_ds01.nc"), lidar data("Geach_ds02.nc"), and NAVGEM reanalysis output ("Geach_ds03.nc").

Image and lidar data were taken aboard the PMC Turbo instrument described in Fritts et al. (2019) "PMC Turbo: Studying Gravity Wave and Instability Dynamics in the Summer Mesosphere Using Polar Mesospheric Cloud Imaging and Profiling From a Stratospheric Balloon". Images contain metadata: balloon location, altitude, and pointing, and image exposure time.

NAVGEM reanalysis model is described in Eckermann et al. (2018) "High-Altitude (0–100 km) Global Atmospheric Reanalysis System: Description and Application to the 2014 Austral Winter of the Deep Propagating Gravity Wave Experiment (DEEPWAVE)". Data consists of vertical profiles from 50-100 km of meridional winds, zonal winds, temperatures and buoyancy frequency.
Keywords: Gravity waves; Polar mesospheric clouds